From recording discrete actions to studying continuous goal-directed behaviours in team sports - Correia, V.; Araújo, D.; Vilar, L.; Davids, K. (Journal of Sports Sciences, 2013)
This paper highlights the importance of examining interpersonal interactions in performance analysis of team sports, predicated on the relationship between perception and action, compared to the traditional cataloguing of actions by individual performers. We discuss how ecological dynamics may provide a potential unifying theoretical and empirical framework to achieve this re-emphasis in research. With reference to data from illustrative studies on performance analysis and sport expertise, we critically evaluate some of the main assumptions and methodological approaches with regard to understanding how information influences action and decision-making during team sports performance. Current data demonstrate how the understanding of performance behaviours in team sports by sport scientists and practitioners may be enhanced with a re-emphasis in research on the dynamics of emergent ongoing interactions. Ecological dynamics provides formal and theoretically grounded descriptions of player-environment interactions with respect to key performance goals and the unfolding information of competitive performance. Developing these formal descriptions and explanations of sport performance may provide a significant contribution to the field of performance analysis, supporting design and intervention in both research and practice.